The Effects of Neoadjuvant Chemoradiation in Locally Advanced Rectal Cancer—The Impact in Intratumoral Heterogeneity - Bettoni, Fabiana; Masotti, Cibele; Corrêa, Bruna R.; Donnard, Elisa; dos Santos, Filipe F.; São Julião, Guilherme P.; Vailati, Bruna B.; Habr-Gama, Angelita; Galante, Pedro A. F.; Perez, Rodrigo O.; Camargo, Anamaria A. (Frontiers in Oncology, 2019)
Purpose: Intratumoral genetic heterogeneity (ITGH) is a common feature of solid tumors. However, little is known about the effect of neoadjuvant chemoradiation (nCRT) in ITGH of rectal tumors that exhibit poor response to nCRT. Here, we examined the impact of nCRT in the mutational profile and ITGH of rectal tumors and its adjacent irradiated normal mucosa in the setting of incomplete response to nCRT. Methods and Materials: To evaluate ITGH in rectal tumors, we analyzed whole-exome sequencing (WES) data from 79 tumors obtained from The Cancer Genome Atlas (TCGA). We also compared matched peripheral blood cells, irradiated normal rectal mucosa and pre and post-treatment tumor samples (PRE-T and POS-T) to examine the iatrogenic effects of nCRT. Finally, we performed WES of 7 PRE-T/POST-T matched samples to examine how nCRT affects ITGH. ITGH was assessed using Mutant-Allele Tumor Heterogeneity score (MATH score). Results: Rectal tumors exhibit remarkable ITGH that is ultimately associated with disease stage (MATH score stage I/II 35.54 vs. stage III/IV 44.39, p=0.047) and lymph node metastasis (MATH score N0 35.87 vs. N+ 45.79, p=0.026). We also showed that nCRT does not introduce detectable somatic mutations, nor alters the clonal structure of the irradiated mucosa. Comparison of PRE-T and POST-T matched samples revealed a significant increase in ITGH in 5 out 7 patients and MATH scores were significantly higher after nCRT (median 41.7 vs. 28.8, p-value=0.04). Finally, in POST-T tumors we observed the expansion of tumor cell subpopulations carrying deleterious mutations in genes associated with response to nCRT. Conclusions: nCRT increases ITGH and may result in the expansion of resistant tumor cell populations in residual tumors. The risk of introducing relevant somatic mutations in the adjacent mucosa is minimal. However, non-responsive tumors may have potentially worse biological behavior when compared to their untreated counterparts.